Highly efficient modified lead oxide electrode using a spin coating/electrodeposition mode on titanium for electrochemical treatment of pharmaceutical pollutant. (April 2019) - Boukhchina, Sahar; Akrout, Hanene; Berling, Dominique; Bousselmi, Latifa
Abstract: In this study, Ti/TiO2 /PbO2 anodes consisting of a PbO2 coating growth on the TiO2 interlayer deposited on titanium substrates were prepared combining different deposition technics: electrochemical method using anodization (Anod), electrodeposition (EL), and sol gel spin coating (SG). Different kinds of anodes have been tested for the removal of ampicillin, a pharmaceutical pollutant, from water. The structure and the surface morphology of the prepared multiple coatings were characterized by scanning electron microscopy and Energy-Dispersive X-ray spectroscopy respectively. Electrochemical impedance spectroscopy was also investigated in order to study the electrocatalytic activity of the anodes. The performance of the electrodes was evaluated through high performance liquid chromatography and chemical oxygen demand (COD) measurements. It was noticed that ampicillin could be mineralized by anodic oxidation process using Ti/TiO2 /PbO2 anodes. The best results were obtained for Ti/TiO2 SG /PbO2 EL as anode with a 64% of COD removal after 300 min of treatment and a fast decrease in the amount of ampicillin was reached after almost one hour. Experimental results demonstrate that Ti/TiO2 SG /PbO2 EL anode presents the best ability for the degradation of ampicillin through anodic oxidation compared to the Ti/TiO2 SG /PbO2 SG and Ti/TiO2 Anod /PbO2 EL electrodes. Graphical abstract: Image 1 Highlights: Ti/TiO2 /PbO2 electrodes were prepared by various combined deposition methods. Anodic oxidation was investigated for removal of ampicillin from wastewaters. Mixing sol gel and electrodeposition produces a promising anode. Highly efficient removal of ampicillin is obtained with Ti/TiO2 SG /PbO2 EL anode.